Magnetic asynchronous nova V1500 Cyg in an "EARLY" and a "MEADLE" post-nova state - Pavlenko, E. P. (Одеські астрономічні публікації, 2017)
A detailed analysis of photometric observations of magnetic nova V15OO Cyg in the ”early” (1978-1988) and ”middle” post-nova state (2000-2002) is presented. The brightness of Nova varies mostly with orbital 0.139613-day and Spin-orbit 8-day beat phases. The periodogram constructed for 1980-1984 data shows a strong peak at the orbital frequency (7 .163d-1) and reveals the presence of three sideband frequencies 2worb - wspin , 2wspin - worb and 3wspin - 2worb, indicating the spin-orbit asynchronism (The spin period is taken from measurements of Schmidt, Liebert and Stockman (1995)).The later (2000-2002) data show the presense of spin modulation in R band while these of the early quiescent state - not. The typical beat light curve profile is one-humped, and seldom it could be two-humped one. The all available timings of minima and maxima obtained since 1978 agree both with long-term orbital period increasing and with constant but slightly reduced its value (0.1396129 day). The timings of orbital maxima and minima sometimes show dependence on the beat phase during almost half beat period. The nature of beat modulation is still unclear, although the periodical brightening of accretion disk and / or accretion stream could occur depending on the orientation of magnetic white dwarf axis in binary.